The Impact of Reaction Lights-Based Shadow Training on Foot Agility in Badminton Players at Pelangi Pontianak City - Ade Rahmat; Ashadi Cahyadi (Inspiree)
The  purpose  of  the study. The  purpose  of  this  study  was  to find  out  the  effect  of  reaction  light  trainingand  shuttle  run  on  footwork  agility  in  PB  badminton  participants Pelangi Pontianak City.